Unveiling the hidden story of anemia among Indian Muslim women: a comprehensive analysis from 1998 to 2021 - Hashmi, Zeenat; Singh, Ashish (Frontiers in Nutrition, 2025)
BackgroundIron deficiency among women of reproductive age, driven by factors such as inadequate dietary intake, menstrual blood loss, and heightened iron demands during pregnancy, remains a global public health concern. This research focuses on the prevalence of anemia among Muslim women in India over the last two decades, with a particular focus on disparities and trends.MethodsAnemia among Muslim women of reproductive age (15–49 years) is studied using the four rounds of the National Family Health Survey (NFHS-2 to NFHS-5) to analyze the trends and disparities using bivariate cross-tabulations, concentration index, P/R ratios, and odds ratios across different socioeconomic factors. This study analyzes data from 212,837 Muslim women of reproductive age, collected through four rounds of the National Family Health Survey between 1998 and 2021.ResultsThe findings reveal a concerning upward trend from 48.77 to 55.6% (1998–2021) in anemia prevalence among Muslim women in India. Anemia is consistently found to be highest in the age group of 15–19 across all the surveys and reported to be 59.14% in NFHS-5. Geographically, the Northeastern and Eastern regions exhibit the highest anemia prevalence rates, at 72.12 and 60.5% in 1998–99, respectively, which decreased to 41.41 and 55.95% in 2015–16, but again rose by 17.74 and 8.72% in 2019–21, respectively. The Western region increased from 37.6% in 1998–99 to 51.76% in 2019–21. Furthermore, rural areas witness a strikingly higher anemia prevalence among women, exceeding urban areas by over 8%. The Scheduled Caste/Scheduled Tribe (SC/ST) populations consistently bear the highest anemia burden. Economic disparities are evident, as wealth quintiles and education attainment display a transparent gradient, with the poorest quintile and no education consistently having the highest odds of anemia.ConclusionThe socially disadvantaged groups, economically backward and less educated women, have constantly shown the highest prevalence of anemia for the period of the past two decades. The policies to improve public health should specifically focus on the most vulnerable sections of society. There is a need to modify existing public policies and improve population health in the context of the most vulnerable sections in developing countries.